52 Werke aus der Sammlung des 20. Jh. Museum Kurhaus Kleve. - De Werd, Guido; Geisselbrecht-Capecki, Ursula; Grass, Matthias; Kratz, Paul; Palmen, Manfred; Thelosen, Karl; Voss, Jens (Kleve : MKK (Museum Kurhaus Kleve) - Ewald Mataré Sammlung, 1997)
Arman ; Beuys, Joseph ; Boltanski, Christian ; Campendonk, Heinrich ; Chamberlain, John ; Christo ; Deacon, Richard ; Erben, Ulrich ; Fischli & Weiss ; Förg, Gunther ; Fritsch, Katharina ; Getlinger, Fritz ; Gilbert & George ; Götz, K.O. (Karl Otto) ; Gursky, Andreas ; Haese, Günter ; Heerich, Erwin ; Klein, Yves ; Kounellis, Jannis ; Lamers, Hanns ; Mataré, Ewald ; Maywald, Willy ; Merz, Mario ; Mucha, Reinhard ; van Ofen, Michael ; Oldenburg, Claes ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Polke, Sigmar ; Richter, Gerhard ; Rollins, Tim & K.O.S. ; Ruff, Thomas ; Schön, Andreas ; Schoofs, Rudolf ; Schütte, Thomas ; Stadtbäumer, Pia ; Struth, Thomas ; Thorn Prikker, Johan ; Wall, Jeff ; Zins, Günther
biografie
Duits
boek